2017
DOI: 10.1016/j.bjorl.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic scoring of solid thyroid nodules: effects of nodule size and suspicious cervical lymph node

Abstract: Sonographic scoring of thyroid nodules is an effective method for predicting malignancy. The authors suggest including associated pathologic node in the scoring criteria. Further studies with larger cohorts will provide more evidence about its importance in sonographic scoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…The US features for PTCs included in our present study were based on the ATA guidelines (2) and other previous related studies (1,11,14). Previous studies have shown that several US features, such as nodular margins, blood flow distribution, hypoechoic appearance, and microcalcification are associated with PTC malignancy, which was consistent with our multivariate analysis (15,16).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The US features for PTCs included in our present study were based on the ATA guidelines (2) and other previous related studies (1,11,14). Previous studies have shown that several US features, such as nodular margins, blood flow distribution, hypoechoic appearance, and microcalcification are associated with PTC malignancy, which was consistent with our multivariate analysis (15,16).…”
Section: Discussionsupporting
confidence: 88%
“…Ultrasonographic-guided FNAB is used to diagnose suspicious nodules for thyroid cancer (2). However, there are some disadvantages, such as inadequate sampling, high cost, invasiveness, indeterminate cytology in some cases, and operator dependency (13,14). Thus, accurate PTC diagnosis using only US is very valuable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, nodule was smaller in malignant group than in benign group. When divided them into two groups by 20 mm, there was no statistically significantly difference in malignancy rate, which was similar to Unsal’s result 17 . Therefore, nodule size was excluded from independent risk factors of intermediate-risk TNs in binary multivariate logistic regression analysis in our study.…”
Section: Discussionsupporting
confidence: 85%
“…By contrast, Unsal et al . 17 thought nodule size ≥2 cm was not distinctive for diagnosis of malignancy. In the present study, nodule was smaller in malignant group than in benign group.…”
Section: Discussionmentioning
confidence: 99%